Uniaxial compressive stability of laminated composite plate with localised interfacial degeneration - Kam, Cheezhou (Maney Publishing, 2014)
Motivated by general observation that it is practically impossible to achieve a perfect attachment between two originally separated materials, this paper examines numerically the influence of localised imperfect bonding at interface on the buckling response of fully fixed laminated composite plates, in the existence of uniaxial compression. The present work focuses on the buckling analysis of a two-layered laminate using the finite element formulation, in which each layer was meshed employing a locally contributing lamina sub-element, whereas the interface lied in between was modelled using a well-defined virtually zero-thickness interface element. To simulate the interfacial degeneration, a degeneration ratio R was conveniently prescribed. The present work has an advantage of permitting the simulation of deteriorated interface in a locally perturbed manner, differs from existing literatures that modelled mostly in a global sense. It is found from the current study that the normalised critical buckling load decreases, which indicates an increased degree of instability, corresponding to the rise in the degeneration ratio. Also, delaminated condition (R = 1), either isolated or otherwise, is the most critical scenario with an approximately 70% performance discount from that of R = 0.9. There exist, in addition, a variety of stability reduction trends when inducing different fibre orientations for the top lamina relative to that of the bottom. High dependencies of buckling modes on the degenerated area (Ar) and distance ratios (-r) have also been exhibited.